2015
DOI: 10.1371/journal.pone.0132661
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 Promotes Motility, Invasion, and Sprouting of Lymphatic Endothelial Cells

Abstract: Tumor-associated lymphatic vessels actively participate in tumor progression and dissemination. ADAM17, a sheddase for numerous growth factors, cytokines, receptors, and cell adhesion molecules, is believed to promote tumor development, facilitating both tumor cell proliferation and migration, as well as tumor angiogenesis. In this work we addressed the issue of whether ADAM17 may also promote tumor lymphangiogenesis. First, we found that ADAM17 is important for the migratory potential of immortalized human de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Our results demonstrated that CSE, 3-MST, and CBS were expressed in adipocytes, consistent with the results of previous studies [13, 14]. Both in adipocytes [15] and in human umbilical vein endothelial cells [25], high glucose significantly inhibited the expression of CSE and production of H 2 S. In the present study, we found that high glucose decreased the expression of CSE and 3-MST, as well as the endogenous H 2 S production, but CBS expression was not affected by high glucose. These results indicate that decreasing H 2 S production and CSE, 3-MST expression could stimulate the expression of ADAM17 and the production of sFlt-1 in adipocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrated that CSE, 3-MST, and CBS were expressed in adipocytes, consistent with the results of previous studies [13, 14]. Both in adipocytes [15] and in human umbilical vein endothelial cells [25], high glucose significantly inhibited the expression of CSE and production of H 2 S. In the present study, we found that high glucose decreased the expression of CSE and 3-MST, as well as the endogenous H 2 S production, but CBS expression was not affected by high glucose. These results indicate that decreasing H 2 S production and CSE, 3-MST expression could stimulate the expression of ADAM17 and the production of sFlt-1 in adipocytes.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Mężyk‐Kopeć et al . reported that silencing of a disintegrin and metalloprotease 17 (ADAM17) affected the levels of TGF‐β2 and TGF‐β3 in a human dermal lymphatic endothelial cell line, but did not affect TGF‐β1 expression . Furthermore, Olave et al .…”
Section: Discussionmentioning
confidence: 99%
“…Signaling events involving EGFRs and the processes governing lymphangiogenesis are closely intertwined. EGFR and HER2 are expressed on human LECs associated with skin, 176,177 while EGFR has been shown to be expressed in the intra-and peritumoral lymphatic vessels of oral squamous cell carcinoma 178 and the peritumoral lymphatics of colon F I G U R E 6 Schematic of EGF pathway target sites of FDA-approved antiangiogenic drugs Notes: EGFR (also known as ERBB1 and human epidermal growth factor receptor 1) and ERBB2 (also known as HER2/NEU) are the main therapeutic targets of currently available antiangiogenic drugs. ERBB2 lacks the ability to bind growth factor ligands and forms heterodimers with EGFR, ERBB3, or ERBB4.…”
Section: Compared To That Of Normal Endothelial Cells Tumor-associatmentioning
confidence: 99%
“…185 For example, A disintegrin and metalloprotease 17 increase heparin-binding epidermal growth factor shedding by LECs, resulting in increased LEC invasion, migration, and tube sprouting. 177 Silencing of A disintegrin and metalloprotease 17 in LECs and treatment with an EGFR inhibitor resulted in both decreased motility and sprouting. 177 Finally, dual inhibition of transforming growth factor beta and EGFR/HER2 using lapatinib suppresses the growth and metastasis of pancreatic ductal adenocarcinoma, which expresses many lymphangiogenic factors.…”
Section: Compared To That Of Normal Endothelial Cells Tumor-associatmentioning
confidence: 99%
See 1 more Smart Citation